2016
DOI: 10.1016/j.jhazmat.2016.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Removing hydrochloric acid exhaust products from high performance solid rocket propellant using aluminum-lithium alloy

Abstract: Hydrochloric acid (HCl) pollution from perchlorate based propellants is well known for both launch site contamination, as well as the possible ozone layer depletion effects. Past efforts in developing environmentally cleaner solid propellants by scavenging the chlorine ion have focused on replacing a portion of the chorine-containing oxidant (i.e., ammonium perchlorate) with an alkali metal nitrate. The alkali metal (e.g., Li or Na) in the nitrate reacts with the chlorine ion to form an alkali metal chloride (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…However, its application has often been restrained due to the native dense oxide layer (Al 2 O 3 ) passivating on the surface, hindering the diffusion of oxygen throughout Al particles in the combustion process [ 5 , 6 , 7 ]. Meanwhile, the combustion process of Al particles usually accompanies ignition delay, incomplete combustion, and so on [ 8 , 9 , 10 ]. Moreover, the larger the size of Al particles is, the longer the path of heat conduction will be [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, its application has often been restrained due to the native dense oxide layer (Al 2 O 3 ) passivating on the surface, hindering the diffusion of oxygen throughout Al particles in the combustion process [ 5 , 6 , 7 ]. Meanwhile, the combustion process of Al particles usually accompanies ignition delay, incomplete combustion, and so on [ 8 , 9 , 10 ]. Moreover, the larger the size of Al particles is, the longer the path of heat conduction will be [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Details pertaining to the propellant formulation/mixing as well as characterization of the fuel additives (e.g., particle size distributions, scanning electron microscopic imaging of particles) can be found in Ref. [29]. In summary, the neat aluminum powder was equiaxed in morphology and had a mean particle size (arithmetic) of 17.1 µm.…”
Section: Solid Propellant Formulationmentioning
confidence: 99%
“…The shattering tendency of single Al-Li particles (10 wt.% lithium) has been observed by Blackman et al [25], though there is no publication showing its usage in an energetic material formulation. Recent concurrent work [29] has shown that there are both environmental and performance benefits to using Al-Li alloy (20 wt.% lithium) as an APCP fuel additive (performance metrics that are generally considered mutually exclusive).…”
Section: Introductionmentioning
confidence: 99%
“…Since HE-MOFs are an emerging class of energetic material and possess very regular channels, introducing a dinitramide ion could increase [12] the sensitivity to mechanical stimulation, perhaps owing to excess compression of functional groups onto a limited backbone. Some powerful anions (azides or perchlorates) could cause serious environmental pollution [15][16][17], which restrict the range of application. Hence, finding suitable groups for high-energy MOFs remains a challenge.…”
Section: Introductionmentioning
confidence: 99%